THE ADJECTIVE AND ITS TYPES IN THE BOOK “WASHÔYÂ AL-ABÂ LIL ABNÂ” BY MUHAMMAD SHAKER AL-ISKANDARI: A GRAMMATICAL ANALYTICAL STUDY - Budiman, Agus; Nabila, Wardah Hani; Ismail, Mohammad; Sakinah, Khoirus; Muttaqin, Rokhmat (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2024)
The study of Nahwu, a branch of Arabic grammar, focuses on changes in word endings related to i'rab (inflection) and bina (construction), as well as sentence structure. Within Nahwu, the concept of tawabi’ refers to words that follow another in agreement with case, definiteness, and other grammatical aspects. Tawabi’ is categorized into na’at (adjective), taukid (emphasis), badal (substitute), and athaf (conjunction). This research specifically analyzes na’at and its types in the book